Diarrheal disease, sanitation, and culture in India - Mohanty, Aatishya (2023)
The health burden of childhood diarrhea in India has been a major public health concern. This study examines the role of the individualism-collectivism dichotomy in the prevalence of diarrhea in children under the age of five in India. Using subnational data on rice suitability to measure collectivism, we provide evidence that collectivism is negatively associated with the prevalence of childhood diarrhea across 618 Indian districts. We find that the mechanism works through improvements in water and sanitation. Collectivism propagates values of interdependence, cooperation and collective action which increases safe water and sanitation practices, thereby reducing the prevalence of diarrhea in children.